The Role of Mergers and Acquisitions in the Strategic Integration of Entrepreneurship - E. V. Chadina (Управленческие науки)
The article is devoted to the role of mergers and acquisitions (M&A) in the strategic integration of entrepreneurship. Mergers and acquisitions can be considered as business transactions, as they are aimed at generating income due to changing both external and internal environment of the company. The process of merging or acquiring as an entrepreneurial idea lies in obtaining synergy effect through the merger of assets of economic entities. The subject of the research is the settlement of mergers and acquisitions transactions as a tool of integration of Russian entrepreneurship. The article presents the results of the statistical study characterizing mergers and acquisitions in Russia and abroad, their main trends as well as the role of the state in the process. While examining the issues of mergers and acquisitions and their public regulation, attention is paid to the methods of business valuation and their characteristics in Russian and foreign practice. Statistics processing is carried out which allows to give quantitative and qualitative characteristics of mergers and acquisitions, identify their role in the strategic process of entrepreneurship integration, as well as to determine the regulatory role of the government in this process. The article reveals the problems arising in the M&A market. The conclusion is drawn that the activity of Russian companies in the M&A domestic and global markets declined slightly over the past period, as well as the aggregate volume of foreign purchases of Russian assets.